Constructing Feature Models Using Goal-Oriented Analysis - Uno, K.; Hayashi, S.; Saeki, M. (2009 Ninth International Conference on Quality Software, 2009)
This paper proposes a systematic approach to derive feature models required in a software product line development. In our approach, we use goal graphs constructed by goal-oriented requirements analysis. We merge multiple goal graphs into a graph, and then regarding the leaves of the merged graph as the candidates of features, identify their commonality and variability based on the achievability of product goals. Through a case study of a portable music player domain, we obtained a feature model with high quality.